Time-related effects of general functional training in spinal cord-injured rats - Miranda, Taisa Amoroso Bortolato (2012)
OBJECTIVES: This prospective, randomized, experimental study with rats aimed to investigate the influence of general treatment strategies on the motor recovery of Wistar rats with moderate contusive spinal cord injury. METHODS: A total of 51 Wistar rats were randomized into five groups: control, maze, ramp, runway, and sham (laminectomy only). The rats underwent spinal cord injury at the T9-T10 levels using the NYU-Impactor. Each group was trained for 12 minutes twice a week for two weeks before and five weeks after the spinal cord injury, except for the control group. Functional motor recovery was assessed with the Basso, Beattie, and Bresnahan Scale on the first postoperative day and then once a week for five weeks. The animals were euthanized, and the spinal cords were collected for histological analysis. RESULTS: Ramp and maze groups showed an earlier and greater functional improvement effect than the control and runway groups. However, over time, unexpectedly, all of the groups showed similar effects as the control group, with spontaneous recovery. There were no histological differences in the injured area between the trained and control groups. CONCLUSION: Short-term benefits can be associated with a specific training regime; however, the same training was ineffective at maintaining superior long-term recovery. These results might support new considerations before hospital discharge of patients with spinal cord injuries.